C.E. Credit. Effect of Steam Sterilization on Accuracy of 3D Printed Implant Surgical Guides: A Pilot Study - Daniel Rexin; Daniela Avila; Alexander Castillo; Kevin Moreno; Emily Tan; Sunee Limmeechokchai; Joseph Lee; Udochukwu Oyoyo; So Ran Kwon; Joseph Y. Kan; Jaime L. Lozada; Robert A. Handysides; et al. (Journal of the California Dental Association, 2024)
Background 3D printed implant surgical guides are designed to improve implant placement accuracy. However, they are a potential source of contamination during implant surgery and therefore require sterilization to prevent post-surgical infection. This study evaluated the effect that steam sterilizing 3D printed implant surgical guides has on the accuracy of fully guided implant placement.Methods 3D printed models were prepared with an edentulous site at the right maxillary central incisor. A surgical guide was designed and fabricated to place a bone level implant at this edentulous site. Ten implants were placed with surgical guides, followed by ten placed with the same guides after autoclave sterilization at 134°C for 6 minutes. Implants were scanned and analyzed using three-dimensional analysis software. The implant platform position, apex position, and angulation were evaluated before and after sterilization of the surgical guides.Results There were statistically significant deviations of implant platform and apex in the x-axis (bucco-lingual), y-axis (mesio-distal), and implant angulation (Wilcoxon signed-rank test, p < .05). There was no statistically significant deviation in the occluso-gingival height of the implant.Conclusions Steam sterilization has a statistically significant effect on the accuracy of fully guided implant placement using 3D printed surgical guides. The buccolingual deviation of the implant apex is clinically significant (mean = 1.22 mm).Practical Implications Dentists should exercise caution when using steam heat (i.e. autoclaving) to sterilize 3D printed implant surgical guides. Alternative options such as cold sterilization may be more appropriate.Continuing Education Credit Available The practice worksheet is available online in the supplemental material tab for this article. A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20.